ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ADOBE FLASH CS6 - Laila Raudatul Fauziah (Universitas Yudharta Pasuruan, 2020)
This study aims to describe the results of the needs analysis for the development of learning media based on Adobe Flash CS6. This research is a qualitative descriptive study using survey methods to identify the needs of students and teachers in learning assessment. In this study, needs analysis refers to the achievement of student learning outcomes, problems faced by students, and the media needed in the learning assessment process. This research uses observation and interview methods in collecting data. Observations and interviews were conducted for grade X students of basic graphic design subjects at SMKN 8Padang. The results showed that: 1) completeness of student learning 2) Interactive learning media needed on computer subjects and basic networks. The results of this study concluded that students need interactive learning media in learning activities. Thus, this research was used in designing learning based on Adobe Flash CS6